Perception and Consumer Behavior of Halal Product Toward Purchase Decision in Indonesia - Much Djunaidi; Cut Baby Ayu Oktavia; Ratnanto Fitriadi; Eko Setiawan (Jurnal Teknik Industri, 2021)
Indonesia is a country with a majority Muslim population. Therefore, Indonesian consumers have to be more thorough in assuring halal guarantees. One of some identities as a Muslim is consuming halal products. Various factors can affect consumers in purchasing halal products. However, the consumption of halal-certified products is still relatively low.  This study was intended to analyze the factors that influenced consumer perceptions in purchasing halal products. A case study was carried out on the coffee product, one of Indonesia's most popular culinary products.  The data were collected based on a survey of 170 respondents who live in Surakarta, Central Java Province, and are Muslim. This study suggested that the factors that significantly influenced the purchase were the variables of religiosity, halal label certification, and product prices. In contrast, the variables of halal awareness and brand image had no significant effect. Thus, the five variables simultaneously had a significant positive effect on purchasing decisions for halal products.